2014
DOI: 10.1007/s11010-014-2253-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA-PKcs deficiency sensitizes the human hepatoma HepG2 cells to cisplatin and 5-fluorouracil through suppression of the PI3K/Akt/NF-κB pathway

Abstract: The aim of the present study was to investigate the effects of DNA-PKcs deficiency on the chemosensitivity of human hepatoma HepG2 cells to cisplatin (CDDP) and 5-fluorouracil (5-Fu), and to explore the underlying molecular mechanism. After transfection with DNA-PKcs siRNA or control siRNA, HepG2 cells were exposed to combination treatment of CDDP and 5-Fu. The cell viability, DNA damage, cell apoptosis, intracellular reactive oxygen species and glutathione (GSH) level, expression of apoptosis related proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…PRKDC is a member of the phosphatidylinositol-3-kinase family 18 . Previous reports have shown that PRKDC is important for AKT activation 19 , 20 . The results of LC-MS/MS showed that KRT80 may interact with PRKDC, so Co-IP assay was performed to test the prediction (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…PRKDC is a member of the phosphatidylinositol-3-kinase family 18 . Previous reports have shown that PRKDC is important for AKT activation 19 , 20 . The results of LC-MS/MS showed that KRT80 may interact with PRKDC, so Co-IP assay was performed to test the prediction (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…These findings suggest that the Akt/NF-κB pathway may be able to mediate P-gp expression. Moreover, DNA-PKcs is a member of the PIKK family and is involved in Akt/NF-κB pathway activation (18). Therefore, we postulate that DNA-PKcs is involved in P-gp expression via the Akt/NF-κB pathway in CD133 + MG-63 cells.…”
Section: Discussionmentioning
confidence: 90%
“…Overexpression of DNA-PKcs is found in various malignancies, which is associated with poor prognosis (16,17). However, inhibition of DNA-PKcs sensitizes cells to chemotherapy in various tumor cells including OS (10,18,19). This indicates that DNA-PKcs is correlated with chemoresistance in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the PI3K family members, DNA-PK plays an important role in NHEJ to repair DSBs, which are a major mechanism of CDDP cytotoxicity (23). A previous study demonstrated that suppression of DNA-PKcs results in sensitization of HepG2 cells to CDDP treatment (33). In the present study, the western blot results revealed that miR-101 overexpression markedly reduced the expression of DNA-PKcs, as well as phosphorylation of Akt and mTOR.…”
Section: Discussionmentioning
confidence: 99%